1998
DOI: 10.1021/jf9704726
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Cucumbers Fermented in Low-Salt Conditions

Abstract: Volatile compounds present in cucumbers fermented in 2% salt were analyzed using purge and trap concentration followed by GC-MS. Thirty-seven volatile compounds were identified from over 100 peaks detected using GC-MS. Most of the identified compounds did not change during fermentation. However, the ability of disrupted cucumber tissue to produce (E,Z)-2,6-nonadienal and 2-nonenal, the two most important volatiles in fresh cucumber odor, decreased during fermentation. In addition, linalool increased to levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
(18 reference statements)
2
25
0
Order By: Relevance
“…Further manual inspection of the data and comparison with retention indices reported in the literature resulted in the identification of 137 volatile compounds in fermented cucumber brine (Table 3). Comparison of these metabolites with previously reported volatile compounds in fermented cucumber brines (Zhou and McFeeters 1998; Marsili and Miller 2000) indicated that this method may be more sensitive in the detection of plant terpenoids, esters, alcohols, highly volatile aldehydes, and light hydrocarbons as greater numbers of these compounds were found in the present study. Several volatile compounds previously identified in fermented cucumber brines using 1D GC‐MS on nonpolar columns were also found in this study, including butanol, pentanol, hexanol, octanol, 2‐pentanol, 2‐heptanol, 2‐ethyl‐1‐hexanol, eucalyptol, α‐terpineol, phenylethyl alcohol, hexanal, nonanal, 2‐heptenal, benzaldehyde, acetone, acetic acid, butanoic acid, hexanoic acid, linalool oxide, 2‐methoxy‐3‐(1‐methylethyl) pyrazine, and dimethyl disulfide (Zhou and McFeeters 1998; Marsili and Miller 2000).…”
Section: Resultssupporting
confidence: 75%
“…Further manual inspection of the data and comparison with retention indices reported in the literature resulted in the identification of 137 volatile compounds in fermented cucumber brine (Table 3). Comparison of these metabolites with previously reported volatile compounds in fermented cucumber brines (Zhou and McFeeters 1998; Marsili and Miller 2000) indicated that this method may be more sensitive in the detection of plant terpenoids, esters, alcohols, highly volatile aldehydes, and light hydrocarbons as greater numbers of these compounds were found in the present study. Several volatile compounds previously identified in fermented cucumber brines using 1D GC‐MS on nonpolar columns were also found in this study, including butanol, pentanol, hexanol, octanol, 2‐pentanol, 2‐heptanol, 2‐ethyl‐1‐hexanol, eucalyptol, α‐terpineol, phenylethyl alcohol, hexanal, nonanal, 2‐heptenal, benzaldehyde, acetone, acetic acid, butanoic acid, hexanoic acid, linalool oxide, 2‐methoxy‐3‐(1‐methylethyl) pyrazine, and dimethyl disulfide (Zhou and McFeeters 1998; Marsili and Miller 2000).…”
Section: Resultssupporting
confidence: 75%
“…(Z)-6-nonenal (Z6-9:al), (Z)-6-nonen-1-ol (Z6-9:1-ol), nonanal (9:al), and 1-nonanol (9:1-ol)], in a rotating outdoor olfactometer (Experiment 3). Different letters represent significant differences (P<0.05) between the mean numbers of flies caught (ANOVA, followed by Tukey's HSD) and Wasternack 2002), and have been found previously in both fresh and fermented cucumbers (Kemp et al 1974;Zhou and McFeeters 1998). The predominant volatile isolated from fresh blended cucumber is E2Z6-9:al, which is also the most important compound in producing the characteristic cucumber smell perceived by humans (Forss et al 1962;Schieberle et al 1990).…”
Section: Discussionmentioning
confidence: 56%
“…The odor threshold for (E,Z)-2,6-nonadienal has been estimated to be 0.01 ppb (5), whereas the threshold for (E)-2-nonenal is somewhat higher at about 0.08 ppb (6). These extremely low thresholds are several 100,000-fold lower than the amount present when fresh cucumbers are blended (7,8). The olfactory sense has trouble accommodating a 100-fold difference between the threshold and the concentration which saturates the receptor (9).…”
Section: Introductionmentioning
confidence: 95%